Thermogravimetric research into composites based on the mixtures of polypropylene and modified polyamide - Krasinskyi, Volodymyr; Kochubei, Viktoria; Klym, Yurii; Suberlyak, Oleh (Eastern-European Journal of Enterprise Technologies, 2017)
We established in the present work the regularities for obtaining homogeneous nanocomposites based on the mixture of PP/PA-6 with montmorillonite modified using PVP. In these nanocomposites, PA-6 and MMT contribute to the increase in thermal resistance of the material, while PVP improves compatibility between polar PA-6 and hydrophobic PP. The goal of the present work was to investigate by applying the methods of thermogravimetric analysis a correlation between thermal characteristics of the newly-created nanocomposites based on the mixture of PE/PA-6 with montmorillonite, modified using PVP, and to determine the optimal composition of a nanocomposite with enhanced thermal resistance and a wide temperature interval of the viscous-fluid state. On the basis of experimental data, it was found that the mixtures of polypropylene with polyamide modified by the montmorillonite-polyvinylpyrrolidone mixture are distinguished by the higher thermal resistance compared with the starting PP. It is established that at a content of the modified polyamide in the mixtures with polypropylene within 30 % by weight, samples of the composite are characterized by the highest thermal resistance ‒ weight loss of such composites in a temperature range of 218‒322 ºC is only 7.1 %, temperature of the onset of thermo-oxidation destruction is 300 ºC. It is shown that the developed nanocomposites have wider temperature intervals of the viscous-fluid state – 126–300 ºC. This makes it possible, by changing the modes of processing, to influence the structure and properties of products, especially taking into account the difference in crystallization of the material depending on the conditions and the method of processing. It is established that the most suitable for application and processing is the mixture of polypropylene with modified polyamide in the ratio 70:30 % by weight, respectively